Kavisnâme-i Menzilât (1B – 51A) inceleme – metin- sözlük- dizin - Arık, Serap (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Türk Dili ve Edebiyatı Anabilim Dalı / Türk Dili ve Edebiyatı Bilim Dalı, 2016)
Bu çalışmada, Kavsnâme-i Menzilât adlı eserin 1B-51A varakları incelenmiştir. Eserde okçuluktan, menzil taşlarından ve okçulardan bahsedilmektedir. Metinde Arapça ve Farsça sözcükler olmasına rağmen dili, sade ve anlaşılırdır. Çalışmaya başlarken önce metin okunmuş, çeviri yazıyla aktarılmış ve daha sonra sözlüğü ve dizini yapılmıştır. Daha sonra da metin biçimsel olarak incelenmiştir. Çalışmaya; özet, içindekiler, önsöz, kısaltmalar ve giriş bölümüyle başlanmıştır. Giriş bölümünde yazarın hayatı hakkında bilgi verildikten sonra "Kavsnâme"den, "Türk Okçuluk Tarihi"nden, "Menzil Taşlarının Yerleri"nden, "Okun Özellikleri"nden, "Yay Yapımı"ndan bahsedilmiştir. Daha sonra metnin genel ve biçim özelliklerinden, bahsedilmiştir. Ayrıca Eski Anadolu Türkçesi hakkında bilgi verilmiştir. I. Bölümde metnin çeviri yazısı, II. Bölümde metnin biçim bilgisi ve III. Bölümde ise sözlük ve dizin yer alır. Biçim bilgisi; yapım ekleri ve çekim ekleri diye ikiye ayrılmıştır. Dizinde ise kişi adları ve yer adları bulunmaktadır. Çalışma, sonuç ve kaynaklar bölümleriyle sona ermiştir. Çalışmanın ekine ise metnin tıpkıbasımı konulmuştur.
Kavi̇snâme-i̇ Menzi̇lât (1B – 51A) analysis - text -dictionary - index
he thesis deals with the folios 1B-51A of the work titled Kavisnâme-i Menzilât (Archery Book on Ranges). The work is on archery, menzil (range) stones ("target" or "medal" stones), and archers. Although Arabic and Persian vocabularies are heavily used in the text, the language is still plain and comprehensible. The author of this present thesis has read the original text, transcribed it, and then prepared a dictionary and an index based on the original. A stylistic analysis of the text later followed. The thesis starts with an abstract, a table of contents, a preface, a list of abbreviations, and an introduction. After presenting the biography of the original author, the introduction section deals with "Kavsname" (book on archery), "The History of Turkish Archery", "The Locations of Menzil Stones" (range/target/medal), "Arrow Specifications", and "Bow Construction". General and stylistics features of the text are later analysed. Additionally, the thesis presents brief information on Old Anatolian Turkish. The section one is the transcribed text, the section two discusses the stylistic components of the same text, and the section three presents a dictionary and an index. The stylistic components are further divided into two sections: derivational and inflectional suffixes. The index is a list of persons and places. The thesis ends with a conclusion and a section of bibliography. In the appendix is a scanned version of the original text.
Keywords: Kavsnâme; Hacı Hasan B.; Hacı Bahtiyar; okçuluk; ok; yay; Türk dili; biçim bilgisi; writing on archery; book on archery; archery; arrow; bow; Turkish language; morphology